A Flat-Gain Double-Pass Amplifier with New Hafnia-Bismuth-Erbium Codoped Fiber. (May 2018) - Al-Azzawi, Alabbas A.; Almukhtar, Aya A.; Reddy, P. H.; Dutta, D.; Das, S.; Dhar, A.; Paul, M. C.; Zakaria, U. N.; Harun, S. W.
Abstract : An efficient and compact double-pass optical fiber amplifier is demonstrated using a newly developed hafnia bismuth erbium co-doped fiber (HBEDF) as a gain medium. The HBEDF is fabricated using a modified chemical vapor deposition in conjunction with solution doping. The fiber has an erbium ion concentration of 12500 ppm. At the optimum length of 0.5 m, the HBEDF amplifier (HBEDFA) achieves a flat gain of 26 dB with a gain variation of less than 1.5 dB within a wavelength region from 1530 to 1560 nm when the input signal and pump power are fixed at −30 dBm and 140 mW, respectively. On the other hand, at the input signal power of −10 dBm, the HBEDFA also achieves a flat gain of 14.2 dB with a gain variation of less than 2.5 dB within a wide wavelength region from 1525 to 1570 nm. Compared with the conventional zirconia erbium co-doped fiber based amplifier, the proposed HBEDFA obtains a more efficient gain and lower noise figure. For an input signal of −30 dBm, the gain improvements of 6.2 dB and 4.8 dB are obtained at 1525 nm and 1540 nm, respectively.